Ocean water-leaving radiance measurements by the Joint Polar Satellite System - Mineart, G. M.; Furgerson, J. A. (2012 Oceans-Yeosu, 2012)
Measurements of ocean remote sensing multispectral optical reflectance by the Joint Polar Satellite System (JPSS) have become increasingly important to the National Oceanic and Atmospheric Administration (NOAA) in plans for satisfying operational requirements for ocean and coastal observations. Such observations are used to derive water-leaving radiance information from which operational applications of importance to public health, safety, and commerce depend, including the detection and monitoring of harmful algal blooms. The higher NOAA priority stems from the recent loss or advanced age of legacy ocean color missions combined with the absence of supporting multispectral or hyperspectral sensing capabilities in other planned Earth observing satellite systems. The JPSS capability will provide ocean remote sensing reflectance in the five visible wavelength bands of the Visible Infrared Imager-Radiometer Suite (VIIRS) from which normalized water-leaving radiance, inherent optical properties, and Chlorophyll-a concentration may be derived. VIIRS near-infrared wavelength bands are used to calculate the required atmospheric corrections and account for the 80-90% of the top-of-atmosphere radiance. The associated JPSS data product performance requirements have matured in comparison to heritage polar satellite requirements. Enhancements to the JPSS requirements include expanded measurement ranges for Chlorophyll-a and optical scattering and absorption, application of measurement accuracy and precision requirements exclusively to the VIIRS visible blue band, a prescription for normalized water-leaving radiance errors in the contributing visible bands so that they are spectrally correlated as observed in heritage data, an extension of the minimum ocean depth subject to accuracy and precision requirements to 30 m, and additional delivery of retrieved data in regions classified by the VIIRS Land-Water Mask as Coastal and Inland Waters. Preliminary science validation results using initial VIIRS data from the Suomi National Polar-orbiting Partnership, a risk-reduction mission for JPSS, indicate excellent potential for fully satisfying operational requirements for ocean color observations.